Acute Effects of Percussive Therapy on the Posterior Shoulder Muscles Differ Based on the Athlete’s Soreness Response - Jack H Trainer; Matthew Pascarella; Ryan W Paul; Stephen J Thomas (International Journal of Sports Physical Therapy)
# Background